Safety assessment for a shield tunnel in a liquefiable deposit using a practical dynamic effective stress analysis. (August 2019) - Lu, Chih-Chieh; Hwang, Jin-Hung
Abstract: Shield tunnels are widely constructed throughout urban areas with most of their sections being fully or partially embedded in liquefiable deposits. The possible damage to shield tunnels caused by soil liquefaction should be considered in their seismic design. Thus, this paper proposes a FDM-based analysis method to study this issue. Several dynamic time history analyses were performed for a shield tunnel embedded at different positions in ground with a liquefiable layer. It was found that the liquefied soil behaves like a fluid, and the tunnel uplifts due to buoyancy if the tunnel is fully embedded in a liquefied soil deposit. However, if the tunnel is only partially embedded in the liquefied deposit, with its top or bottom section in a non-liquefied deposit, the interaction behavior is quite complex and differs from that of a tunnel fully embedded in liquefied soil. To check the safety of the lining, the internal forces of the lining were monitored and compared with its strength curves throughout the shaking history. The proposed framework can be used as a reference for a practical engineer to consider the dynamic behavior of a shield tunnel in a liquefiable deposit. Highlights: The study suggests a procedure to assess the seismic behavior of a shield tunnel in the ground with a liquefiable deposit. The safety assessment of the tunnel was performed by comparing the lining internal forces with the capacity curves. The location of a shield tunnel would affect its dynamic behavior in a liquefiable deposit during seismic loading.